Double-sided coaxial circuit QED with out-of-plane wiring - Rahamim, J; Behrle, T; Peterer, M; Patterson, A; Spring, P; Tsunoda, T; Manenti, R; Tancredi, G; Leek, P (AIP Publishing, 2017)
Superconducting circuits are well established as a strong candidate platform for the development of quantum computing. In order to advance to a practically useful level, architectures are needed which combine arrays of many qubits with selective qubit control and readout, without compromising on coherence. Here, we present a coaxial circuit quantum electrodynamics architecture in which qubit and resonator are fabricated on opposing sides of a single chip, and control and readout wiring are provided by coaxial wiring running perpendicular to the chip plane. We present characterization measurements of a fabricated device in good agreement with simulated parameters and demonstrating energy relaxation and dephasing times of T1 = 4.1 μs and T2 = 5.7 μs, respectively. The architecture allows for scaling to large arrays of selectively controlled and measured qubits with the advantage of all wiring being out of the plane.